Case Study of The Ethical Issues of Child Labor in Chocolate Business in The West Africa Regions - Yusnaidi Yusnaidi (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2018)
Abstract : This case study was conducted to identify ethical aspect of chocalate industry which related to the used of child labour in farming and harvesting process in West Africa region. The case study identified the issue through secondary data collected from online resources. It is a descriptive article to describe the condition of unethical issues by employing children in the cocoa plantation and factory. It is a giant industry which involved giant companies and big market as well as huge number of the customers. However the benefit was not always distributed to all of the participants or contributors of the industry. Especially for those who work at the cocoa plantation in west Africa region. There are two parties which raised the ethical issues of employing child labour in the chocalate industry, the supporting and contrary parties. It is a dilemma. Both sides have strong argument to deal with the issue and the method to solve it. However it could be concluded the child labor are increased because of four main problems, poverty,education, culture and political issue. In many case these issues are combined to contributed in the used of child labour. In conclusion it needs comprehensive programs involved all the stakeholders of the chocolate industry to take the responsibility to improve the quality of life of the child and families in the west africa especially those who are living around the cocoa plantation. They are just the children who should have the life as the children, similar right as other children around the world have. Keywords: business ethics, child labour, chocolate industry